Semantic Study On The Simeulue Island Culture On Nandong - Ningsih, Rahayu Anzar (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This research is mainly investigated to determine the concept of semantics andthe function of Nandong Smong poetry for the people of Simeulue Island.The theoretical study that underlies this research is the semantic theory proposed by Chaer (2010: 59) which divides meaning into lexical meaning, connotative meaning, and grammatical meaning. And for functional use function theory.The method used in this research is descriptive qualitative method. The research subject in this study was the poetry of Nandong Smong. The research object in this study was the semantics (lexical meaning, connotative meaning, and grammatical meaning) of Nandong Smong poetry in cultural arts on the island of Simeulue. Data collection techniques in this research are library techniques, observation techniques, and note taking techniques. The research instruments in this study were data recording cards and reference books. The data analysis technique in this research is content analysis. Furthermore, in data presentation techniques, the author uses informal methods. Based on the discussion of the data and the results of this study, it shows that in nandong smong poetry there are semantics related to lexical meaning, connotative meaning, and grammatical meaning. Functionally, nandong smong is used in various Simeulue cultural activities such as weddings, circumcisions, welcoming guests, cultural parties, performances, and others. Meanwhile, the main function of nandong smong is to inform the symptoms and phenomena of the tsunami and how to save oneself from the tsunami disaster, plus other functions such as: communication, cultural preservation, entertainment.